Géolocalisation des sources fiscales pré-révolutionnaires : la quadrature du cercle - Florent Hautefeuille (Bulletin du Centre d’Études Médiévales d’Auxerre)
The multiplication of tax sources from the late Middle Ages makes possible the spatialization of data which, for previous periods were difficult to cross with the archaeological sources without adequate tools. This paper incorporates the results of two programs funded by the ANR and the RNMSH. The aim was to provide tools for inventory and geolocation of different sources from seignorial land map and pre revolutionary cadasters (Architerre project), to registers without plans such as “terriers” or southern “compoix” (Modelespace project). The first project is primarily a website which converges to the information from different conservation services and offer a search interface with a spatial input. The tool allows to decompartmentalize funds and make available sources which are usually difficuld to use. The second component is the result of collaboration between loboratories of archaeologists, historians and mathematicians. It aimed to provide a method for comparing the settlement’s dynamics from the modeling of tax sources in the form of adjacency graph. The paper describes the method for switching informations from a terrier or a compoix to a geolocated graph.